Can Islamic Law Mitigate Corruption? A Maqāṣid-Based Critique of Village Governance in Indonesia - Agung Nugroho Reformis Santono; Luqman Hakim; Anfasa Naufal Reza Irsali (Pustaka Peradaban, 2025)
Law No. 3 of 2024 Concerning Villages is introduced as a strategic policy to strengthen village self-reliance, yet its implementation faces persistent challenges from structural poverty and corruption that hinder development. This article evaluates how the maqāṣid al-sharī'ah approach can be utilized to assess the effectiveness of this law in alleviating poverty and mitigating corruption in rural areas. This research employs a qualitative method with a text analysis approach to the law's articles, complemented by a review of secondary data from government reports and relevant academic studies. The analysis reveals that the Village Law holds substantial potential to fulfill maqāṣid al-sharī'ah, particularly in safeguarding wealth (ḥifẓ al-māl) and life (ḥifẓ al-nafs), through transparent village financial management and enhanced community capacity. However, weaknesses in supervision and policy implementation remain significant obstacles to combating corruption. Therefore, more consistent implementation efforts aligned with maqāṣid al-sharī'ah principles are crucial to ensure sustainable, just, and prosperous village development. This study ultimately proposes the concepts of maqāṣid qāryah (at the level of maqāṣid al-khāshāh) and maqāṣid as-siyasatul qāryah (at the level of maqāṣid juz'iyyah) as a robust conceptual framework for addressing poverty and mitigating corruption in these areas.